Sexual Stigma Patterns Among Nigerian Men Who Have Sex with Men and Their Link to HIV and Sexually Transmitted Infection Prevalence. - Rodriguez-Hart, Cristina; Musci, Rashelle; Nowak, Rebecca G.; German, Danielle; Orazulike, Ifeanyi; Ononaku, Uchenna; Liu, Hongjie; Crowell, Trevor A.; Baral, Stefan; Charurat, Man; For The Trust/rv368 Study Group (AIDS & Behavior, 2018)
Sexual stigma facilitates the spread of HIV and sexually transmitted infections (STIs) but little is known about stigma affecting Nigerian men who have sex with men (MSM). We assessed patterns of sexual stigma across Nigerian MSM and their relationship to HIV and STIs. Data were collected from the TRUST/RV368 Study, a prospective cohort of 1480 Nigerian MSM enrolled from March 2013 to February 2016 using respondent driven sampling. Structural equation modeling was utilized to assess the association between stigma classes and HIV and STI prevalence, adjusting for participants’ characteristics. A dose-response association was found between stigma class and HIV prevalence (27, 40, 55%, overall χ2 p < 0.001) and STI prevalence (15, 21, 24%, overall χ2 p = 0.011). These data suggest that stigma mitigation strategies, combined with increased engagement of MSM and retention in the HIV care continuum, need to be a component of interventions focused on reducing HIV transmission risks among MSM in Nigeria.